2011
DOI: 10.1155/2011/123527
|View full text |Cite
|
Sign up to set email alerts
|

Growing Teratoma Syndrome and Peritoneal Gliomatosis

Abstract: The growing teratoma syndrome (GTS) is defined as a detection of an enlarged mass during or after chemotherapy treatment for germ cell tumor. We report a case of an 18-year-old girl treated for growing teratoma syndrome after chemotherapy for malignant germ cell tumor of the ovary associated with peritoneal gliomatosis. Chemotherapy induced normalisation of alpha-fetoprotein rate whereas there was an enlargement of the mass. Subsequent complete resection was performed, and the patient remained in good control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…[3] A review of the literature reported by Chou et al had found 65 cases of GP, which have favorable prognosis after surgical treatment. 6 The mechanism of implantation is unknown and two theories to explain the origin of GP have been proposed. In one glial implant arise from the teratoma and in the other, pluripotent stem cells in the peritoneum or adjacent mesenchyme undergo glial metaplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] A review of the literature reported by Chou et al had found 65 cases of GP, which have favorable prognosis after surgical treatment. 6 The mechanism of implantation is unknown and two theories to explain the origin of GP have been proposed. In one glial implant arise from the teratoma and in the other, pluripotent stem cells in the peritoneum or adjacent mesenchyme undergo glial metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…In one glial implant arise from the teratoma and in the other, pluripotent stem cells in the peritoneum or adjacent mesenchyme undergo glial metaplasia. [6] Recent molecular studies of glial implants have shown that they are genetically different from an ovarian tumor but have same genetic patterns as patient. 4 Substances produced by a tumor result in metaplastic transformation of peritoneal or subperitoneal tissue into glial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…23 In the literature review of Chou et al, the prognosis of 65 cases with gliomatosis peritonei has been reported good after primary surgical treatment. 15,26 In patients with immature teratoma including mature glial implants, malignant tumor lesions may be observed late after the first surgery. Therefore, long-term follow-up of these patients is recommended.…”
Section: Immature Teratoma Of the Ovary With Gliomatosis Peritoneimentioning
confidence: 99%
“…Rarely GTS may follow treatment of nongerminomatous germ cell tumor of the pineal gland (5) and immature teratoma of the ovary (6)(7)(8). Fewer than 20 cases of GTS have been reported in female individuals after a diagnosis of immature ovarian teratoma.…”
mentioning
confidence: 99%
“…This entity was first described in 1982 by Logothetis et al (9) in the setting of nonseminomatous testicular germ cell tumors, and may be mistaken clinically for relapse or recurrence of immature teratoma. Patients with immature teratoma may also develop gliomatosis peritonei (6,10), which further complicates the clinical picture.…”
mentioning
confidence: 99%